New synonymy in the wheat thrips, Haplothrips tritici (Thysanoptera: Phlaeothripidae) - Minaei, Kambiz; Mound, Laurence (Zootaxa, 2014)
The wheat thrips, Haplothrips tritici, is known from across eastern Europe and adjoining areas of Asia into western Europe and north Africa, and is widely regarded as a pest of cultivated cereal crops, particularly of Triticum but also of Hordeum (Özsisli 2011). The identity of this thrips species is not in doubt, but a closely similar species, Haplothrips cerealis, was described from Egypt (Priesner 1939), and subsequently recorded between southeastern Europe and Iran (see Minaei & Mound 2008). Priesner based this species on an unspecified number of specimens of both sexes, collected from the ears of cultivated wheat at “Wadi Gederât, Sinai”, and did not designate a holotype. Minaei and Mound (2010) indicated that they considered the records of cerealis from Iran to be based on misidentifications of tritici, but they suggested that further studies were required to determine if there is any evidence that these names represent different species in other countries. The problems arise because the published descriptions of, and comparisons between, the two species are confusing and sometimes contradictory. The objective of this report is to examine the published literature, and to consider this in relation to observed structural variation in recently collected samples as well as specimens in museums that are variously labeled as one or other of these two species.